Turning Rice into Pilau: the Art of Video Narration in Tanzania - Krings, Matthias (Intermédialités / Intermediality, 2012)
This essay investigates the remediation of foreign films as it is currently practised in Tanzanian video parlours, by video narrators interpreting these films into Kiswahili. Video narration is a means to appropriate and domesticate foreign audiovisual material in terms of primary orality. Video narration reverses the hierarchy of original and copy insofar as the moving images of the original become mere illustrations of governing local narratives. Whether performed live or mediatized as voice-over on DVD or VHS cassette, video narration exposes the reality of film as mediated, heightens awareness of the viewing situation and fosters the critical inquiry of the audience.